(untitled) (Research, Society and Development, 2022)
Objective: To map existing knowledge about deleterious habits such as pacifiers and bottle feeding and the implications on the development of children aged 0-6 years. Review Method: Scoping review protocol according to the Joanna Briggs Institute method. Published and unpublished bibliographic materials will be considered, according to the following inclusion criteria: to report the types of harmful habits (concept) occurring in the population of children aged 0-6 years (population) and their impact on child development (context). A detailed individual search strategy will be used for each database: Virtual Health Library (VHL), PubMed and Scopus. Two reviewers will screen the titles and abstracts, read the full texts, and extract data from the included material. Presentation and Interpretation of Results: The results included in this scoping review will be classified into conceptual categories of analysis from Thematic Categorical Analysis, grounded in Bardin’s content analysis.